Design type-2 fuzzy for superconducting magnetic energy storage to enhance frequency transient response - Abdillah, Muhammad; Bagus Laksono, Arie; Indriani Pertiwi, Nita; Aryo Nugroho, Teguh; Setiadi, Herlambang; Araminta Jasmine, Senit; Evanda Putra, Naufal (Bulletin of Electrical Engineering and Informatics, 2025)
Renewable energy has become a new trend in power systems. Renewable-based power plants such as wind power systems and photovoltaics. This paper proposed a novel method for inertia emulation based on superconducting magnetic energy storage (SMES). To get better inertia support for the system, a type-2 fuzzy controller is used as the SMES controller. An area power system is used as the test system to investigate the performance of type-2 fuzzy controller on SMES. Time domain simulation is carried out to show the efficacy of the proposed method. From the simulation results, it is found that the proposed controller can reduce the overshoot of frequency by up to 20% compared to the type-1 fuzzy controller. It is also hoped that the proposed method can be used as a reference of the Industrial people.